Analisis Distribusi Ikan Teri (Stolephorus sp ) Tawar Kering di Pasar Segiri Kota Samarinda - Elam, Cindy Maria; Abdusysyahid, Said; Gunawan , Bambang Indratno (Jurnal Pembangunan Perikanan dan Agribisnis, 2025)
The research was conducted with the aim of knowing marketing channels and minimizing marketing margins. Therefore, the analysis of marketing share margin and profit margin is important to find out the components with the highest marketing costs. So that a solution can be found and the marketing costs can be minimized, so that the final price can still be reached by the consumer. The research was conducted at Pasar Segiri Samarinda for 11 months from September 2022 to July 2023. The sampling method used was a targeted sampling method with 15 respondents. The used analysis method of data analysis is a method of qualitative and quantitative analysis. The qualitative data analysis process describes the marketing channel descriptively.           Based on the results of the study, it was revealed that the marketing channel for dried anchovies at Segiri Market in Samarinda City is marketing channel level 0 of 18,000/kg, marketing channel level I of 19,000/kg, marketing channel level II of 20,000/kg, was marketing channel level III of 20,000/kg. An analysis of the size of price range, profit and distribution efficiency (farmer share) received by marketing players for Dried Fresh Anchovies in Segiri Market. Samarinda City is a collector of Rp. 2,000/kg, a retailer of Rp. 2,500/kg. Kg and a dealer for 3,000 Rp./Kg. Efficiency is a marketing channel level II of 0,8 and marketing channel level III of 0,33.